Madagascar: public health situation on the "Big Island" at the beginning of the 21st century - Andrianarisoa, A C E; Rakotoson, J; Randretsa, M; Rakotondravelo, S; Rakotoarimanana, R D; Rakotomizao, J; Aubry, P (Médecine tropicale, 2007)
The main public health issue in Madagascar at the beginning of the 21st century still involves transmissible infectious diseases including re-emerging diseases such as bubonic plague and emerging diseases such as HIV/AIDS, dengue fever and Chikungunya virus infection. Health and hygiene especially access to clean water is still poor especially in rural areas. No improvement in the public health situation with regard to malaria, schistomosomiais or cysticercosis as well as non-infectious diseases such as protein-energy malnutrition is expected within the next decade.